Link between pay for performance incentives and physician payment mechanisms: Evidence from the diabetes management incentive in Ontario - Jasmin Kantarevic; Boris Kralj (Institute for the Study of Labor (IZA), 2012)
Pay for performance (P4P) incentives for physicians are generally designed as additional payments that can be paired with any existing payment mechanism such as salary, fee-for-service, and capitation. However, the link between the physician response to performance incentives and the existing payment mechanisms is still not well understood. In this paper, we study this link using the recent primary care reform in Ontario as a natural experiment and the Diabetes Management Incentive (DMI) as a case study. Using a comprehensive administrative data and a difference-indifferences matching strategy, we find that physicians in a blended capitation model are more responsive to the DMI than physicians in an enhanced fee-for-service model. We show that for a given payment mechanism this result implies that the optimal size of P4P incentives varies negatively with the degree of supply-side cost sharing. These results have important implications for the design of P4P programs and the cost of their implementation.
urn:nbn:de:101:1-2012080812112
Keywords: I10; I12; I18; 330; pay for performance; physician remuneration; diabetes management; Ärzte; Leistungsentgelt; Vergütungssystem; Diabetes; Gesundheitsreform; Ontario (Provinz)